Lasers in Esthetic Dentistry: Soft Tissue Photobiomodulation, Hard Tissue Decontamination, and Ceramics Conditioning - Karen Müller Ramalho; Patrícia Moreira de Freitas; Ana Cecília Correa-Aranha; Marina Stella Bello-Silva; Roberta Marques da Graça Lopes; Carlos de Paula Eduardo (Hindawi Limited, 2014)
The increasing concern and the search for conservative dental treatments have resulted in the development of several new technologies. Low and high power lasers can be cited as one of these new technologies. Low power lasers act at cellular level leading to pain reduction, modulation of inflammation, and improvement of tissue healing. High power lasers act by increasing temperature and have the potential to promote microbial reduction and ablation of hard and soft tissues. The clinical application of both low and high power lasers requires specific knowledge concerning laser interaction with biological tissues, so that the correct irradiation protocol can be established. The present case report describes the clinical steps of two metal-ceramic crowns development in a 60-year-old patient. Three different laser wavelengths were applied throughout the treatment with different purposes: Nd:YAG laser (1,064 nm) for dentin decontamination, diode (660 nm) for soft tissue biomodulation, and Er:YAG laser (2,940 nm) for inner ceramic surface conditioning. Lasers were successfully applied in the present case report as coadjutant in the treatment. This coadjutant technology can be a potential tool to assist treatment to reach the final success.